Clinical, Epidemiological and Therapeutic Characteristics of Patients Admitted for a Bronchial Asthma Attack - Juan Carlos Yanes Macías; Juan Camilo Díaz Ceballos; Mercedes Fonseca Hernández; Ileana García Rodríguez; Caridad Llul Tombo; Daimy Tio González (Revista Finlay, 2020)
Background: bronchial asthma is the prevalent chronic non-communicable disease in childhood, in its evolution it presents crises triggered by multiple factors, related to the host and the environment. Objective: to describe the clinical, epidemiological and therapeutic characteristics of bronchial asthma crises at the Paquito González Cueto University Pediatric Hospital in Cienfuegos, during 2015 and 2016. Method: a descriptive, and correlational study was carried out on a series of cases at the Paquito González Cueto University Pediatric Hospital in Cienfuegos in the period from January 1st, 2015 to December 31st 2016, in which were included the patients who leave with the diagnosis of a bronchial asthma crisis. The data were obtained from the clinical history of the patients. The variables were analyzed: age, sex, skin color, classification of the asthmatic disease, severity of the crisis on admission, and form of drug distribution. Descriptive statistics procedures were applied, such as the determination of the frequency of occurrence and the percentages. Results: the most affected age group was under 3 years old (35.8 %), with a slight predominance of males (55 %) and white skin color (57 %), the highest number of admission corresponded to the months of epidemic rise, the minor persistent form (53.6 %) and the moderate seizures (94.6 %) predominated, the 64.4 % had no control treatment. Conclusions: most of the patients received inadequate treatment for the crisis in the emergency room and the ward; in addition, the control treatment was inadequate or non-existent in almost half of the patients.